1925 Ind. Acts 496, § 4 - (:unkn) unknown (My University, 1925)
An Act to Regulate and Control the Possession, Sale, and Use of Pistols and Revolvers in the State of Indiana, § 4: Prohibited felony convicts from possessing or having under their control a pistol or revolver; violates subject to felony conviction and imprisonment of 1-5 yrs.
Keywords: POSSESSION - DANGEROUS PERSONS